HUBUNGAN KADAR GULA DARAH PUASA TERHADAP RESTING HEART RATE PADA PASIEN DIABETES MELITUS 2 PUSKESMAS WARUNG JAMBU - Azzahra Roudhotul Jannah (2023)
Hyperglycemia, a main pathological condition in DM, can be influenced by increased RHR, which is a risk factor for cardiovascular disease. Out of 181 type 2 DM patients registered as members of PROLANIS at Warung Jambu Public Health Center, 90 of them are included in the study as it is important in controlling FBG levels. This study aims to determine the relationship between FBG levels and RHR in type 2 DM patients at Warung Jambu Public Health Center. This study is an observational analytical with a cross-sectional approach on 34 type 2 DM PROLANIS using consecutive sampling technique. FBG levels and RHR was using glucometer and digital sphygmomanometer. Univariate analysis consists of frequency, percentage, mean, and standard deviation of the variable, and bivariate analysis using Spearman's correlation. The results showed that approximately 35.5% of the respondents were in the age range of 61-70 years, predominantly female (79.4%), 52.9% had DM for 1-5 years, with an average fasting blood glucose level of 179.62 mg/dl, and an average RHR of 87.32 bpm. The bivariate analysis indicated a significant relationship between fasting blood glucose levels and RHR in PROLANIS patients at Warung Jambu Public Health Center, with a p-value of 0.001. Higher FBG levels were associated with higher RHR in type 2 DM patients registered in PROLANIS at Warung Jambu Public Health Center. Therefore, patients are advised to participate in PROLANIS activities and take caution in maintaining blood glucose levels to minimize the risk of cardiovascular complications.